2019
DOI: 10.1177/0706743719870513
|View full text |Cite
|
Sign up to set email alerts
|

Vulnérabilité au Trouble Bipolaire: La Piste de la Vitamine D

Abstract: Objectifs : L’étiopathogénie du trouble bipolaire (TB) demeure non encore bien élucidée. Récemment, il a été prouvé que la 25-hydroxy-vitamine D(25OHD) a un rôle anti-inflammatoire et neuroprotecteur. Nos objectifs étaient de mesurer les concentrations plasmatiques de la 25OHD chez des patients atteints de TB en décompensation aigue et de les comparer à celles de patients souffrant de schizophrénie (SCZ) ou de trouble schizo-affectif (TSA) et à celles de témoins sains Méthodes : Il s’agissait d’une étude trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…One study comprising 118 participants found that patients with BD were 470% more likely to be de icient in vitamin D than the general population [124]. In contrast, one cross-sectional study found plasma 25-hydroxy vitamin D levels to be higher in patients with BD who were in a state of decompensation than in healthy controls [125]. There is evidence to suggest that vitamin D supplements may reduce symptoms of depression and mania, although further research is required to determine clinically effective dosages [126][127][128].…”
Section: Bipolar Disorder and Nutrientsmentioning
confidence: 99%
“…One study comprising 118 participants found that patients with BD were 470% more likely to be de icient in vitamin D than the general population [124]. In contrast, one cross-sectional study found plasma 25-hydroxy vitamin D levels to be higher in patients with BD who were in a state of decompensation than in healthy controls [125]. There is evidence to suggest that vitamin D supplements may reduce symptoms of depression and mania, although further research is required to determine clinically effective dosages [126][127][128].…”
Section: Bipolar Disorder and Nutrientsmentioning
confidence: 99%
“…Recent studies have shown that there might be a link between bipolar disorder and vitamin D deficiency [53]. There is little information concerning vitamin D levels and supplementation effects on the course of bipolar disorder; however, there has been a noted increase in 25OHD synthesis during BD decompensation [54]. Other studies have shown a lower level of vitamin D in people with bipolar disorders, but supplementation was not correlated with an improvement in depressive symptoms [55].…”
Section: Bipolar Disordersmentioning
confidence: 99%
“…Receptor-1,25(OH)2D3 antagonizing the effects of the glucocorticoid on hippocampal neurons [59] Lower level of serum Vitamin D is caused by long periods of institutionalization, inactivity, and, therefore, less exposure to sunlight [49] Bipolar disorders Increased 25OHD synthesis during decompensation [54] Lower level of Vitamin D in depressive patients [55] Depression Mechanisms implied are exerting influence on neuroendocrine, immunological, and neurotrophic systems [59] Receptors are localized in the hypothalamus [124] Table 1. Cont.…”
Section: Psychotic Spectrum Diseasesmentioning
confidence: 99%
“…19,20 Therefore, the anti-inflammatory neuroprotective role of vitamin D may preserve axonal integrity in the face of neurodamage, which can be identified as neurofilament light chain (NfL) levels. 10,21 The NfL is a unique biomarker related to axonal damage and neural cell death. It demonstrates promise as a potential marker of neuropsychiatric disease activity and progression associated with cognitive deficit.…”
Section: 4mentioning
confidence: 99%